Admissibility of Lawsuits Based on Interest under Algerian Civil and Administrative Procedures - Yassine, Chami; Ahmad, Ahmad; Muhtar, Mohamad Hidayat; Rivera, Kevin M; Putri, Viorizza Suciani (Jambura Law Review, 2024)
This study examines the impact of interests on the admissibility of civil and administrative lawsuits in Algeria under the Administrative and Civil Procedures Code in the country. The research utilized a normative research method that integrated legal concepts and approaches. It drew on primary legal sources such as laws, regulations, and court decisions, as well as secondary sources including documents, literature, and articles. The study aims to raise awareness among both legal professionals and the general public about the significance of interests in civil lawsuits and how it can impact the admissibility or inadmissibility of lawsuits filed before the court. This will help enhance judicial efficiency by allowing courts to prioritize cases with significant impact on the parties or broader societal relevance. The research manifested that interests are pivotal in determining a lawsuit's validity and that for a lawsuit to be heard, interests must be legal, legitimate, and actual. It also highlighted that the concept of interest in civil lawsuits acts as a crucial mechanism to safeguard the integrity, fairness, and efficiency of the judicial system. Objections based on the unenforceability of interests serve as a key procedural tool, enabling the dismissal of lawsuits that do not meet this criterion. Thus, interest is essential not only for forming the basis of a lawsuit but also for maintaining judicial integrity and effectiveness.